Virtual Reality in (Finnish and British) Museums : A study into its use, role, effectiveness and potential - Jones, Laura (My University, 2021)
This thesis studies the ways in which virtual reality (VR) is currently being used in museums, using select examples from Finland and the United Kingdom. It will illuminate the current uses of VR and how they got to this point; the effectiveness and potential of VR in a museum setting; as well as the role it has in museums. The use of VR in museums is a straightforward look into different ways museums have incorporated this new media technology - although the main focus is on experiences and exhibitions brought to audiences through VR headsets, as these are the most popular and talked-about examples, thus providing a good angle for research. On the other hand, ‘effectiveness’ and ‘potential’ are subjective concepts, but the chapters included will raise and attempt to answer questions on whether VR has affected the number of visitors or their experience in addition to the perspective from museum professionals, as well as whether it could be used in different or prominent ways to increase its value to museums. The final chapter relates to the larger question of what is the role of museums in a changing world and how VR fits into this. The research methods used in this thesis are varied. In addition to academic sources, it consists of largely qualitative research in the form of first-hand observation, informal talks as well as lectures and seminars, a questionnaire and reviewing of documents and news related to the subject. This is partly due to the lack of available material since VR is still considered an emerging field, and partly because the nature of qualitative research seemed to suit the subject matter the best in order to get a more full picture. Therefore a lot of the material used is not from written sources. The approach is also from a micro level, as I use examples of the use of VR from Finnish and British museums to further understand the wider context and landscape - which hopefully provides new interpretations on the material available. By looking at a subject that is still “new” such as VR, the hope is to offer new insight into how museums can utilise VR to its full potential so that it best serves them. There are always contrasting opinions, especially on new subject matter, but, for me, the conclusion to take is that VR can be an effective tool for museums even if it is not crucial - as long as they know how to use it, keeping content at the centre instead of the medium - and as it develops, we have not yet seen all it can do in a museum setting.
Keywords: virtual reality, museum, heritage, new media technology